Ołowiane żołnierzyki, cynkowe trumny. Swietłany Aleksijewicz opowieść o wojnie w Afganistanie i granice świadectwa - Artwińska, Anna (Narracje o Zagładzie, 2021)
The novel Zinky Boys (1989; Polish editions in 2007 and 2015) by Belarusian author Svetlana Alexievich is more than just a story of the Soviet military intervention in Afghanistan (1979–1989) told from the perspective of the soldiers who participated in it. It also confronts readers with the contractual nature of the line that separates “artistic” and “documentary” prose and probes the complexities of the discourse on memory in Russian culture. This article discusses the key motifs of Zinky Boys: “zinc coffins” and “lead soldiers”. It also examines and ponders the reasons for the lawsuit against the author for the publication of passages from the novel. Drawing on Michael Rothberg, Anna Artwińska argues that, in order to be able to understand the drama of the Soviet intervention in Afghanistan, one needs to assume the position of an “implicated subject”, i.e., of a person who understands the need for shared ethical responsibility for traumatic past events, even though they neither participated in those events nor witnessed them.